Histopathological analysis of rats chronically exposed by inhalation to the herbicide 2,4-Dichlorophenoxyacetic acid (2,4-D) (Research, Society and Development, 2021)
The expansion of 2,4-D consumption raises concerns about the environment and especially human health, as exposure to this chemical agent can cause harmful effects to the body. The aim of this research was to histopathologically evaluate the nasal epithelium and the hematological profile of rats submitted to chronic inhaled spraying of the 2,4-D herbicide. Forty adult male Wistar rats were used, divided into 4 groups, namely: Control Group (GC), Low Concentration Group (GBC), Medium Concentration Group (GMC) and High Concentration Group (GAC). The exposure protocol was carried out using 2 boxes connected to 2 ultrasonic nebulizers, which sprayed the herbicide daily for 15 minutes for 6 months. After the exposure period, a blood sample was collected to prepare the blood count and collection and analysis of the nasal epithelium to quantify the mast cells and inflammatory infiltrate. There was a statistically significant difference in relation to the Mean Corpuscular Hemoglobin Concentration (CHCM) values of the GBC when compared to the CG, but the CG had high values and the GBC had values whin the normal range. Regarding the other hematological parameters evaluated, mast cells and inflammatory infiltrate were not observed statistically significant differences in the groups exposed to the 2,4-D herbicide when compared to the CG. Thus, the 2,4-D herbicide showed no toxicity to hematological parameters and nasal epithelium of Wistar rats after chronic inhalation exposure for a period of 6 months when compared to the control group.